PENTINGNYA 1.000 HPK UNTUK MENCEGAH STUNTING DI DESA SUKAMUKTI BOJONGMANGU - Nurita, Firda Putri; Irfan Saputra, Muhammad; Paryati, Ninik; Prasetyo, Setyo (Universitas Islam 45 Bekasi, 2024)
Stunting is a problem of malnutrition in children that lasts a long time. Mothers aged 14-15 years are more likely to have stunting in their children. High stunting can be influenced by the mother's literacy skills or the form of parenting patterns. This Community Service Program aims to increase understanding of the importance of preventing stunting early on in pregnant women and mothers with toddlers in Sukamukti Village, Bojongmangu. This activity was attended by 15 mothers with toddlers and 10 pregnant women. The research method used community education by means of direct observation and socialization with the village secretary, cadres and midwives in Sukamukti Village. Through three stages, namely, pre-test, psychoeducation, evaluation in the form of a post-test. There are final results, namely, before conducting psychoeducation, there was an understanding of 56% and after conducting psychoeducation, there was an increase of 28%. So after the evaluation, the results were 84%.